RESPON PESERTA DIDIK TERHADAP BAHAN AJAR BERSTRUKTUR REFUTATION TEXT TENTANG MOMENTUM DAN IMPULS SMA - Nandaria Nandaria; Haratua Tiur Maria S; Erwina Oktavianty (Universitas Tanjungpura, 2021)
AbstractThis study aims to describe the response of students at using refutation text handbook as teaching materials on momentum and impulse materials. The data were collected questionnaire that was given after learning with refutation text teaching materials ended 32 students of science class at SMA Negeri 5 Pontianak participated for this research. The results showed that the students' responses to refutation text teaching materials obtained an average percentage of eligibility of 83.34% with very high criteria. Thus students responded well to this teaching material with a Refutation Text structure, it greatly increases learning motivation, students have the opportunity to work with friends, they have something new in learning and lessons that are easy to remember.The teaching material in this study is a set of made in the form of refutation text that describes the explanation referring to the misunderstanding of students’ misunderstanding of scientific concepts packaged by schools in order to attract students responses in learning.Keyword: Analysis of Student Response, Momentum and Impulses, Teaching Materials Refutation.